2014
DOI: 10.3389/fendo.2014.00073
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Stress, HPA Axis Adaptation, and Mechanisms Contributing to Later Health Outcomes

Abstract: Stress activates the hypothalamic–pituitary–adrenal (HPA) axis, which then modulates the degree of adaptation and response to a later stressor. It is known that early-life stress can impact on later health but less is known about how early-life stress impairs HPA axis activity, contributing to maladaptation of the stress–response system. Early-life stress exposure (either prenatally or in the early postnatal period) can impact developmental pathways resulting in lasting structural and regulatory changes that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
176
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(181 citation statements)
references
References 182 publications
2
176
1
2
Order By: Relevance
“…Experiments in rats have shown that rats exposed to early life stress show elevated GCs as adults [21]. Similar observations have been made in human subjects who show chronically elevated GCs and altered stress response long after a traumatic event [17]. The effects of stress can therefore be persistent, lasting long after termination of the stressor.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Experiments in rats have shown that rats exposed to early life stress show elevated GCs as adults [21]. Similar observations have been made in human subjects who show chronically elevated GCs and altered stress response long after a traumatic event [17]. The effects of stress can therefore be persistent, lasting long after termination of the stressor.…”
mentioning
confidence: 53%
“…However, after chronic stress and long term elevations of GCs, the effects of GCs are detrimental with neurotoxic, immunosuppressive, and metabolic consequences [17][18][19]. Accordingly, many neuropsychiatric disorders are associated with abnormalities in the HPA axis, with chronically elevated cortisol and reduced sensitivity to GC [20], suggesting stress may contribute to their development.…”
mentioning
confidence: 99%
“…The consequences of early-life (prenatal as well as postnatal) stress on emotional and social behaviors have been a subject of several recent reviews (eg, Sandi and Haller, 2015;Nishi et al, 2014). Here, we summarize in Table form the consequences of chronic early-life adversity provoked by abnormal maternal care in the limited bedding-nesting environment (Gilles et al, 1996;Molet et al, 2014), a model recently adopted and adapted by over 50 laboratories around the world (eg, Raineki et al, 2010;Wang et al, 2011;Bolton et al, 2013;Machado et al, 2013;Maniam et al, 2014;Kohl et al, 2015;Naninck et al, 2015; Table 1). …”
Section: Emotional and Social Consequences Of Early-life Experience Vmentioning
confidence: 99%
“…[12][13][14] Moreover, it also seems sound and acceptable to consider that obesity be mediated through effects on appetite, sleep, and activity. [12][13][14] The (re)activity of the hypothalamic-pituitary-adrenal (HPA)-system plays a role in the course of disorders of anxiety and depression. In the few studies that have investigated the association between anxiety disorders and cortisol levels in children and adolescents, findings have been as inconclusive as in adults.…”
mentioning
confidence: 99%